Quantum changes in Helicobacter pylori gene expression accompany host-adaptation - Chua, Eng-Guan (DNA Res, 2017)
Helicobacter pylori is a highly successful gastric pathogen. High genomic plasticity allows its adaptation to changing host environments. Complete genomes of H. pylori clinical isolate UM032 and its mice-adapted serial derivatives 298 and 299, generated using both PacBio RS and Illumina MiSeq sequencing technologies, were compared to identify novel elements responsible for host-adaptation. The acquisition of a jhp0562-like allele, which encodes for a galactosyltransferase, was identified in the mice-adapted strains. Our analysis implies a new β-1,4-galactosyltransferase role for this enzyme, essential for Le(y) antigen expression. Intragenomic recombination between babA and babB genes was also observed. Further, we expanded on the list of candidate genes whose expression patterns have been mediated by upstream homopolymer-length alterations to facilitate host adaption. Importantly, greater than four-fold reduction of mRNA levels was demonstrated in five genes. Among the down-regulated genes, three encode for outer membrane proteins, including BabA, BabB and HopD. As expected, a substantial reduction in BabA protein abundance was detected in mice-adapted strains 298 and 299 via Western analysis. Our results suggest that the expression of Le(y) antigen and reduced outer membrane protein expressions may facilitate H. pylori colonisation of mouse gastric epithelium.